Content Analysis of English Textbook: Suitability between Skill Focus and Language Features - Annisa Amilia Nur Hidayah; Avrisya Diah Ayunasti; Zukhrufa Zahra Wina Azkia; Rini Estiyowati Ikaningrum (Jurnal VARIDIKA, 2021)
A textbook is one of the important things in supporting the teaching-learning process in high school. The material should follow the learning purposes. In this study, the descriptive qualitative method is used by analyzing the content of the textbook. The results of this research are divided into three parts, Compatibility; Skill Focus; and Language Features. The learning purposes and the materials are compatible. It is lack of skill focus in each skill, and the language features are compatible with the learning purposes. Therefore teachers should be more critical and creative in providing the material and conducting the teaching-learning activity smoothly.